La gimnasia cerebral en la rehabilitación del deterioro cognitivo de los adultos mayores del hogar de ancianos y aislamiento de la ciudad de riobamba, período enero-junio 2013. - Mayorga, Javier (2013)
The Brain Gym is the set of coordinated and combined exercises that encourage and accelerate relearning, of impaired cognitive abilities, potentiate brain neuroplasticity. This research was conducted with 10 elderly patients, 5 men and 5 women nursing home and isolation of the city of Riobamba, the objectives were; evaluate the effects of cerebral gymnastics in rehabilitation of cognitive impairment, impaired cognitive functions identify, apply brain gym exercises and analyze the results. As an instrument of evaluation of higher mental functions test rapid assessment of cognitive functions (ERFC) we were used before and after application of the exercises of cerebral gymnastics, these exercises were applied for 4 weeks from Monday to Friday with a duration 40 minutes a day with a total of 20 sessions. Among the most important results showed they were initially patients had cognitive decline of 29%, after the implementation of the program Brain Gym cognitive impairment was presented by 18%, giving a rehabilitation of 11% of cognitive ability from the patients.